Hepatitis E Virus (HEV) Infection in Hemodialysis Patients: A Multicenter Epidemiological Cohort Study in North-Eastern Greece - Dionysios Kogias; Aikaterini Skeva; Andreas Smyrlis; Efthymia Mourvati; Konstantinia Kantartzi; Gioulia Romanidou; Maria Kalientzidou; Vasiliki Rekari; Eleni Konstantinidou; Parthena Kiorteve; Ioannis Paroglou; Vasileios Papadopoulos; et al. (Pathogens, 2023)
Hepatitis E virus (HEV), a common cause of viral hepatitis in developing countries, is mainly transmitted via the fecal–oral route, but also may be a prevalent hospital-transmitted agent among patients on regular hemodialysis due to parenteral transmission. Previous epidemiological studies among hemodialysis patients in Greece, using different diagnostic techniques, gave conflicting results. Τhe present study aimed to measure the exposure rate of hemodialysis patients of north-eastern Greece to HEV by estimating the overall seroprevalence, and to identify potential risk factors. Serum samples from all patients attending the hemodialysis centers of north-eastern Greece (n = 6) were tested for the presence of anti-HEV IgG antibodies using a modern and sensitive ELISA (Enzyme-linked Immunosorbent Assay) technique (Wantai). In total, 42 out of 405 hemodialysis patients were positive for anti-HEV IgG (10.4%), while all samples were negative for HEV RNA when tested using nested RT-PCR. HEV seropositivity among hemodialysis patients was significantly associated with area of residence and contact with specific animals (pork, deer). No association was found with religion, gender distribution and hemodialysis duration. This study showed an increased seroprevalence of HEV among hemodialysis patients in Greece. Agricultural or livestock occupation and place of residence seem to be independent factors that increase the risk of HEV infection. In conclusion, HEV infection calls for the regular screening of hemodialysis patients regardless of the hemodialysis duration or clinical symptoms.